Perang Arab-Israel - Siti Fauziyah (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2014)
Konflik Arab-Israel dimulai dari ketika orang-orang Yahudi menginginkan sebuah tanah air bagi mereka.